2009
DOI: 10.1029/2008gl036662
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of mineral dust surface as a potential atmospheric renoxification process

Abstract: [1] The nitrate formation on dust particles is considered as a sink for atmospheric NO y (such as HNO 3 ). However mineral dust is shown here to be an effective photocatalyst for transformation of nitrate anions into NO and NO 2 , without involving its photolysis. The photodecomposition of NO 3 À at the surface of synthetic mineral dust samples of SiO 2 , TiO 2 , mixed TiO 2 -SiO 2 and authentic sand doped with 6% NO 3 À was studied by means of a flow-tube at 298 K with UVillumination in the 340 -420 nm range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
157
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(169 citation statements)
references
References 12 publications
7
157
0
Order By: Relevance
“…The difference between the values observed by and by Underwood et al (2001) might be due to saturation effects at the higher pressures noted by . The same likely applies to the study of Li et al (2010) on CaCO 3 performed at NO 2 pressures in the 0.1 mbar range. We therefore recommend the parameterisation obtained by Ndour et al (2009) for Saharan dust, with a large uncertainty .…”
Section: Comments On Preferred Valuesmentioning
confidence: 91%
See 1 more Smart Citation
“…The difference between the values observed by and by Underwood et al (2001) might be due to saturation effects at the higher pressures noted by . The same likely applies to the study of Li et al (2010) on CaCO 3 performed at NO 2 pressures in the 0.1 mbar range. We therefore recommend the parameterisation obtained by Ndour et al (2009) for Saharan dust, with a large uncertainty .…”
Section: Comments On Preferred Valuesmentioning
confidence: 91%
“…The same likely applies to the study of Li et al (2010) on CaCO 3 performed at NO 2 pressures in the 0.1 mbar range. We therefore recommend the parameterisation obtained by Ndour et al (2009) for Saharan dust, with a large uncertainty . Distinctly different mechanisms are suggested for the different substrates and especially in the presence and absence of water.…”
Section: Comments On Preferred Valuesmentioning
confidence: 91%
“…Ndour et al (2009a) have shown that nitrate ions adsorbed onto mixed TiO 2 /SiO 2 and pure TiO 2 can be converted into gaseous NO and NO 2 under UV irradiation. Moreover, it was shown that the interaction of NO 2 with TiO 2 (Monge et al, 2010) and commercial self-cleaning TiO 2 -containing window glass (Langridge et al, 2009) results in the formation of nitrous acid (HONO) in the gas phase, that may have a negative environmental impact (Monge et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the antipolluting nature of the TiO 2 -containing materials was recently questioned (Langridge et al, 2009;Monge et al, 2010;Ndour et al, 2009a). Ndour et al (2009a) have shown that nitrate ions adsorbed onto mixed TiO 2 /SiO 2 and pure TiO 2 can be converted into gaseous NO and NO 2 under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Daytime HONO formation pathways on aerosol and ground surfaces include the photo-enhanced heterogeneous conversion of NO 2 to HONO on TiO 2 (Bedjanian and El Zein, 2012;Langridge et al, 2009;Ndour et al, 2008Ndour et al, , 2009, soot (Ammann et al, 1998;Aubin and Abbatt, 2007;Gerecke et al, 1998;Khalizov et al, 2010;Monge et al, 2010), humic acid (BartelsRausch et al, 2010;Stemmler et al, 2006Stemmler et al, , 2007, and organic films (Brigante et al, 2008;George et al, 2005;Gutzwiller et al, 2002). While we know little about the detailed mechanism, Stemmler et al (2006) proposed that the formation of HONO from NO 2 to HONO conversion on surface-adsorbed humic acid is first order in NO 2 at low NO 2 mixing ratios and linearly dependent on irradiance.…”
Section: Introductionmentioning
confidence: 99%